Germination and seedling growth of ornamental species of Passiflora under artificial shade - doi: 10.4025/actasciagron.v34i1.11623 - Marcel Viana Pires; Alex-Alan Furtado de Almeida; Abel Louro Figueiredo; Fábio Pinto Gomes; Margarete Magalhães Souza (Acta Scientiarum. Agronomy, 2011)
Passiflora morifolia, P. suberosa litoralis, and P. palmeri var. sublanceolata are three wild species with ornamental potential that occur in Brazil. These species were evaluated with the purpose of determining the effects of different shade levels on seedling emergence and initial growth. Treatment with 50% shade resulted in the highest percentage of seedling emergence and the highest emergence speed index for all three species. The 50% shade level was the best condition for growth of P. morifolia and P. palmeri var. sublanceolata seedlings because in this condition, they presented higher growth in relation to control and the other treatments. However, P. suberosa litoralis can be considered a sun species because it grew better in full sunlight and 25% shade, but its growth was stunted at 75% shade. Increased leaf area and specific leaf area were due to changes in leaf dimension and shape in response to an increase in shade levels. These observations related to the initial growth reflect the development and adaptation of adult plants to heterogeneous environmentsenvironments. Therefore, P. morifolia and P. palmeri var. sublanceolata seedlings adapted better to moderate shade conditions, and P. suberosa litoralis seedlings should be cultivated in full sunlight.